Communication strategies of an Arab child with developmental disorders / Maimona Elwan - Elwan, Maimona (2014)
A qualitative case study was conducted on an Arab boy (AE) aged 7 years, who is a native speaker of Aleppine (North-Syrian) dialect to determine his communicative competence and the strategies he uses to compensate for his difficulties. Although having no apparent developmental delay in early childhood, he experienced several unique difficulties in communication, language acquisition and behaviour (i.e. ADHD, and a few autistic traits). The observation technique and several formal and informal assessment procedures were used to collect authentic data from the subject between (6;10 -7;4 years). Checklists adopted in this study are Bishop‟s CCC (1998); Abu Nab‟a‟s Checklist for Language Development in Typical Arab Children; and Grunwell (1985a) PACS and others to fit AE‟s phonological processes in the Aleppine Arabic dialect. Data of different types (Expressive and Receptive) are documented through a few selected tasks to identify his strengths and weaknesses, and to draw a holistic picture of the subject‟s communicative competence. Analysis suggests inconsistent episodes of both acquired dysphasia (Dysnomia) and dyspraxia that is parallel to findings in the clinical and the neurolinguistic literature of brain white matter disorders (i.e. Childhood MS). No signs of Dyslexia or Dysarthria are detected. Analysis also reveals a phonological disorder comprising mainly Metathesis and Substitution at the syllabic level and other unusual processes. The findings reveal AE‟s compensation via positive non-verbal strategies to sustain communication with family members. The communicative types in an idiosyncratic model of paediatric neuropsychiatric co-morbidity are discussed in relation to typical and atypical language theories.